Superior measuring system for calibration of radiation thermometers - Witkowski, Roman; Malinowski, Rafał; Bakoń, Tomasz (Instal, 2020)
This article presents the theoretical foundations, construction and laboratory verification of a prototype test stand for calibration of radiation thermometers with an accuracy better than 0.5°C. The stand was designed and built based on the idea of a virtual instrument. In the designed prototype, the digital processing of measurement data is carried out using a platform with an Arduino hardwear. This enabled calibration of radiation thermometers with any emissivity factor. After verifying the metrological properties of the test stand, the components of the uncertainty budget were determined, and a methodology for calibrating of radiation thermometers and thermal imaging cameras with the measurement range from -20°C to +80°C (in the range most often used by installers) was developed.
Keywords: radiation thermometry; temperature measurements; calibration